Sierra: a power-proportional, distributed storage system - Thereska, Eno; Donnelly, Austin; Narayanan, Dushyanth (Microsoft Research, 2009)
We present the design, implementation, and evaluation of Sierra: a power-proportional, distributed storage system. I/O workloads in data centers show significant diurnal variation, with peak and trough periods. Sierra powers down storage servers during the troughs. The challenge is to ensure that data is available for reads and writes at all times, including power-down periods. Consistency and fault-tolerance of the data, as well as good performance, must also be maintained. Sierra achieves all these through a set of techniques including power-aware layout, predictive gear scheduling, and a replicated shortterm versioned store. Replaying live server traces from a large e-mail service (Hotmail) shows power savings of at least 23%, and analysis of load from a small enterprise shows that power savings of up to 60% are possible.